The Relationship Between Islam and Local Culture in the Passalama' Banua Tradition on Pagurungan Besar Island - Encung Heriyadi; Alfiansyah (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
TraditionPassalama' banuaimplemented and believed as a tradition of pushing logs by the Pagerungan Besar community, a tradition passalama' banua    Previously, it was done by the Mandar tribe before coming to Pagerungan Island. This tradition originates from West Sulawesi because the majority of the population of Pagerungan Besar Island comes from West Sulawesi. The object of this thesis research is the traditions that developed among the people of Pagerungan Island Village regarding Islam and local culture which are carried out in the implementation of traditions.passalama' banua.The method used in this research is an anthropological approach, a descriptive qualitative research type with data collection to support this research carried out by collecting observation data, interviews and documentation. Primary data was obtained from interviews with several informants, namely traditional leaders, religious leaders and the local community. Secondary data is obtained from books, journals, articles and relevant previous research to support research according to facts in the field.The research results obtained were that traditionpassalama' banuais an island salvation tradition on Pagerungan Besar Island as a manifestation of asking for salvation from Allah SWT through the traditional media of the Pagerungan Besar community. Implementation of Islamic values ​​in traditionPassalama' Banuacan be concluded from the existence of an attitude of respect, appreciation, asking for salvation and asking for blessings from Allah SWT through the implementation of traditional activitiespassalama' banua.